The Lead Books of Granada - Drayson, E. author. aut Link
XV, 289 p.
Keywords: The Lead Books of Granada is the first full-length book in English to investigate the story of the remarkable forgeries fabricated in late sixteenth-century Spain and uncovered on the Sacromonte hillside in Granada in 1595. The unearthing of twenty-two lead discs, which contained sayings of the Virgin Mary, St Peter and St James written in Arabic, Latin and Castilian, rocked the whole of Spain and attracted the attention of the Vatican. Heralded as astonishing archaeological discoveries as significant as the Ark of the Covenant, the Lead Books were widely believed to be authentic by the Catholic Church in Spain, yet one hundred years later in 1682, the Vatican condemned them as Islamic heresies, consigning them to oblivion in dusty archives until 2000, when they were returned to Granada. Now published for the first time in paperback, this book evaluates the cultural status and importance of the Lead Books, polyvalent and ambiguous texts that embody many of the dualities and paradoxes inherent in the racial and religious dilemmas of Spain in the sixteenth and seventeenth centuries.